Gastropod Community Structure in Seagrass Ecosystems in the Madong Bay Waters of Bugis Village, Tanjung Pinang City, Riau Islands - Lina Puspita Sari; Adriman Adriman; M. Fauzi M. Fauzi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractSeagrass ecosystem in the Madong Bay is inhabited by numerous aquatic organisms, including gastropods. A research aim to determine the community structure of gastropds in the seagrass ecosystem has been conducted on July – August 2019. Data was collected from 3 stations, there were 2 line transects in each station. In each line there was 4 quadrats (1m x 1m). Gastropods present inside the quadrat were collected manually. Results shown that there was 9 species of gastropods, namely Pirenella cingulate, Cerithium coralium, Drupella margariticola, Nassarius canoldalis, Nerita lineata, Pugilina cochilidium, Strombus canarium, Strombus urceus and Trochus maculatus. The diversity index (H’) was 1.99 – 2.49 (medium), uniformity index (E) was 0.77 – 0.83 (high) and dominance index (C’) was 0.32 – 0.22. Keywords :Pirenella cingulate, diversity index, uniformity index, dominance